2023
DOI: 10.1126/sciadv.ade9585
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 controls iron homeostasis and ferroptosis through HERC2 and VAMP8

Abstract: Enhancing the intracellular labile iron pool (LIP) represents a powerful, yet untapped strategy for driving ferroptotic death of cancer cells. Here, we show that NRF2 maintains iron homeostasis by controlling HERC2 (E3 ubiquitin ligase for NCOA4 and FBXL5) and VAMP8 (mediates autophagosome-lysosome fusion). NFE2L2/NRF2 knockout cells have low HERC2 expression, leading to a simultaneous increase in ferritin and NCOA4 and recruitment of apoferritin into the autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(79 citation statements)
references
References 67 publications
1
41
1
Order By: Relevance
“…Recently, our group showed that Nrf2 regulates iron homeostasis by controlling both ferritin synthesis and degradation as illustrated in Fig. 3 ( Anandhan et al, 2023 ). First, HERC2 , encoding an E3 ubiquitin ligase for NCOA4 (a cargo adapter for ferritin degradation by autophagy [ferritinophagy]) and FBXL5 (an iron-dependent regulator of IRP1/2 that binds to the iron responsive element in the 5’-UTR of FTH1 and FTL mRNA thereby repressing their translation and preventing ferritin synthesis) was identified as a novel Nrf2 target gene.…”
Section: Overview Of Ferroptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group showed that Nrf2 regulates iron homeostasis by controlling both ferritin synthesis and degradation as illustrated in Fig. 3 ( Anandhan et al, 2023 ). First, HERC2 , encoding an E3 ubiquitin ligase for NCOA4 (a cargo adapter for ferritin degradation by autophagy [ferritinophagy]) and FBXL5 (an iron-dependent regulator of IRP1/2 that binds to the iron responsive element in the 5’-UTR of FTH1 and FTL mRNA thereby repressing their translation and preventing ferritin synthesis) was identified as a novel Nrf2 target gene.…”
Section: Overview Of Ferroptosismentioning
confidence: 99%
“…Thus, Nrf2 regulates ferritin protein stability at both the translational and ferritinophagy-dependent turnover levels. Critically, we showed that these two mechanisms are vital to mediating Nrf2-driven resistance to ferroptosis induction in cancer cells, as deletion of Nrf2 resulted in ferritinophagy blockage, NCOA4-dependent recruitment of apoferritin to the autophagosome, an elevated LIP, and enhanced sensitivity to the ferroptosis inducer imidazole ketone erastin ( Anandhan et al, 2023 ). Overall, Nrf2 regulation of iron homeostasis is a critical determinant of a cell’s sensitivity or resistance to ferroptosis, which is independent of its antioxidant function, as discussed below.…”
Section: Overview Of Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that NRF2 regulates the expression of genes controlling ferroptosis. By maintaining iron homeostasis and mitigating lipid peroxidation, NRF2 protects the cancer cells against ferroptotic cell death ( Anandhan et al, 2023 ). By extending this finding, Aryatara Shakya et al discuss the anti-ferroptic function of NRF2, which indicates the feasibility of inhibiting NRF2 to increase the intracellular labile iron pool and thus sensitize cancer cells to ferroptosis.…”
mentioning
confidence: 99%
“…Recent studies have shown that small molecules can induce cancer ferroptosis through ferroptosis center molecules such as GPX4, Xc- system, and NRF2. These compounds that induce ferroptosis have the common characteristic of high iron activity, which provides ideas for drug development ( 8 , 9 ). The papers we included suggest that Wogomin, Manolide, and the compound zoledronic acid can induce ferroptosis in cancer cells.…”
mentioning
confidence: 99%